Genomic Investigation Reveals a Community Typhoid Outbreak Caused by Contaminated Drinking Water in China, 2016 - Hu, Bin; Hou, Peibin; Teng, Lin; Miao, Song; Zhao, Lijiang; Ji, Shengxiang; Li, Tao; Kehrenberg, Corinna; Kang, Dianmin; Yue, Min (Frontiers in Medicine, 2022)
Typhoid fever is a life-threatening disease caused by Salmonella enterica serovar Typhi (S. Typhi) and remains a significant public health burden in developing countries. In China, typhoid fever is endemic with a limited number of reported outbreaks. Recently, the Chinese local Center for Disease Prevention and Control is starting to apply whole genome sequencing for tracking the source of outbreak isolates. In this study, we conducted a retrospective investigation into a community outbreak of typhoid fever in Lanling, China, in 2016. A total of 26 S. Typhi isolates were recovered from the drinking water (n=1) and patients' blood (n=24) and stool (n=1). Phylogenetic analysis indicated the persistence of the outbreak isolates in drinking water for more than 3 months. The genomic comparison demonstrated a high similarity between the isolate from water and isolates from patients in their genomic content, virulence gene profiles, and antimicrobial resistance gene profile, indicating the S. Typhi isolate from drinking water was responsible for the examined outbreak. The result of pulsed-field gel electrophoresis (PFGE) revealed these isolates had identical PFGE pattern, indicating they are clonal variants. Additionally, phylogeographical analysis of global S. Typhi isolates suggested the outbreak isolates are evolutionarily linked to the isolates from the United Kingdom and Vietnam. Taken together, this study highlights the drinking water and international travel as critical control points of mitigating the outbreak, emphasizing the necessity of regular monitoring of this pathogen in China.